Lost Napa Valley - Coodley, Lauren (The History Press, 2021)
"Napa Valley, once known for its cattle and silver mines, has grown into an international wine destination. On the way, many buildings and institutions have vanished. ... Join author and historian Lauren Coodley as she celebrates those once-beloved landmarks in California's Wine Country."--Back cover